Genome-wide association study and fine-mapping on Korean biobank to discover renal trait-associated variants - Dong-Jin Lee; Jong-Seok Moon; Dae Kwon Song; Yong Seok Lee; Dong-Sub Kim; Nam-Jun Cho; Hyo-Wook Gil; Eun Young Lee; Samel Park (The Korean Society of Nephrology, 2024)
Background Chronic kidney disease is a significant health burden worldwide, with increasing incidence. Although several genome-wide association studies (GWAS) have investigated single nucleotide polymorphisms (SNP) associated with kidney trait, most studies were focused on European ancestry. Methods We utilized clinical and genetic information collected from the Korean Genome and Epidemiology Study (KoGES). Results More than five million SNPs from 58,406 participants were analyzed. After meta-GWAS, 1,360 loci associated with estimated glomerular filtration rate (eGFR) at a genome-wide significant level (p = 5 × 10-8) were identified. Among them, 399 loci were validated with at least one other biomarker (blood urea nitrogen [BUN] or eGFRcysC) and 149 loci were validated using both markers. Among them, 18 SNPs (nine known ones and nine novel ones) with 20 putative genes were found. The aggregated effect of genes estimated by MAGMA gene analysis showed that these significant genes were enriched in kidney-associated pathways, with the kidney and liver being the most enriched tissues. Conclusion In this study, we conducted GWAS for more than 50,000 Korean individuals and identified several variants associated with kidney traits, including eGFR, BUN, and eGFRcysC. We also investigated functions of relevant genes using computational methods to define putative causal variants.